The Influence of Education on Employee Performance PT. With The Work of Serving The Field Area - Irvan Malay; Amelia Aisyah Syahrani; April Silvana; Gearaldy Falah Ginting; Suvina Ramadini (Yayasan Multidimensi Kreatif, 2024)
The purpose of this research is to determine and analyze the influence of education on employee performance at PT. WITH WORK SERVING THE Medan Area. Human resources have a very important influence on the realization of organizational goals. Performance in an organization is the answer to the success or failure of the organizational goals that have been set. Education has had an influence on employee performance in order to improve intellectual skills and can provide development of employee human resource potential in accordance with the targets and goals the company wants to achieve. This research aims to identify and analyze whether education influences employee performance at PT. WITH WORK SERVING THE Medan Area. The role of education in improving the quality of human resources is very important. This is very important considering that education is a way out of the problem of bottlenecks in a person's knowledge and skills in their field of work. The influence of education on employee performance has the greatest influence. The suggestion is: remember that education has a significant positive influence and makes a significant contribution to employee performance at PT. BY SERVING THE Medan Area, the company and management need to increase the performance intensity of their employees so that they work at a more significant level of performance.